The Development of Tourism Potentials in Communities for Sustainable MICE Tourism in Nakhon Pathom Province - Chuamuangphan, Nipon; Thongkhum, Krittiya; Wirojnarom, Wanwasa; Kiratikarnkul, Siriporn (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2025)
This research paper "The Development of Tourism Potentials in Communities for Sustainable MICE Tourism in Nakhon Pathom Province" aimed to: (1) assess the potential of community tourism to support MICE (Meetings, Incentives, Conferences, and Exhibitions) tourism, and (2) identify sustainable community tourism management strategies for MICE in Nakhon Pathom’s community tourist sites. Employing qualitative action research methods, the study focused on two communities: Khlong Mahasawat and Thai-Chinese Cultural Tourism Community, Bang Luang, in Nakhon Pathom Province. Data collection tools included focus group discussions, in-depth interviews, and observations, with content analysis and descriptive summarization used for data interpretation. Findings indicated that both communities possess tourism potential across five dimensions (5A’s): natural and cultural attractions, accessibility, diverse activities, comprehensive amenities, and sufficient accommodations. Additionally, sustainable community tourism management for MICE should consider five aspects: (1) safety and accessibility, (2) hospitality and memorable experiences, (3) landscape and facility management, (4) creativity in activity organization, and (5) tourist departure processes. The study also suggests that tourism communities should establish connections in travel routes and activities to diversify services for tourists through network coordination, while considering resource and environmental conservation to achieve sustainable MICE community tourism.